DNA quantification by real-time PCR in different forensic samples. (December 2015) - Martins, C.; Lima, G.; Carvalho, MR.; Cainé, L.; Porto, MJ.
Abstract: The quantification of human DNA is an important procedure since it ensures the competence of the assays carried out in forensic samples. The estimation of the DNA quantity enables the prevention of dissipation of DNA samples used in assays. It's realization by real-time PCR is an attractive assay for quantification of unknown samples. In this study, quantification of human DNA (nuclear and mitochondrial) from three different biological samples (blood, buccal swabs and hair) and different concentrations from control DNA K562 (Promega) was performed using TaqMan ® Universal PCR Master Mix assay and Quantifiler ® Trio DNA Quantification Kit. Based on quantification data, different PCR protocols were tested in order to provide information about the more adequate assay to use. DNA quantification (both nuclear and mitochondrial) is an essential tool since it allows the forensic expert to decide what kind of DNA analysis is going to perform, without lost of sample.